A systematic review and meta-analysis investigating the impact of exercise interventions on heart rate variability in hemodialysis patients - dos Santos Disessa, Henrique [UNESP]; Monteiro, Pedro Henrique Martins; da Silva Zacharias, Vitor [UNESP]; da Costa Rosa, Clara Suemi [UNESP]; Monteiro, Henrique Luiz [UNESP] (Springer Nature, 2024)
Patients with chronic kidney disease have a high incidence of cardiovascular diseases, and autonomic dysfunction has a determinant role in the relevant declines. Physical exercise influences heart rate variability and cardiac autonomic modulation. Thus, our objective was to systematically review, with a meta-analysis, the correlation between physical exercise interventions and alterations in cardiac autonomic modulation in hemodialysis patients. A customized research strategy was used across four databases. The search yielded 392 studies, with eight randomized clinical trials included (396 participants), indicating that the investigated indices favor the intervention group by increasing autonomic activity. The exercise training probably increases the standard deviation of all NN intervals (20.71 ms CI 95% [9.55, 31.87], p < 0.001, I²=95%) compared to the control group and showing an moderate certainty, was the most commonly used index (seven studies). Mean RR (35.57 ms CI 95% [14.56, 56.57], p = 0.91, I²=0%), the root mean square sum of squares of differences between NN intervals (10.55 ms CI 95% [6.75, 14.34], p = 0.37, I²=4%), and LF/HF (0.28 ms (n.u) [0.11, 0.44], p = 0.18, I²=39%) were also in favor of the training group. However, based on the GRADE analysis we are uncertain whether Mean RR can increase after an exercise intervention, as well RMSSD and LF/HF may increase slightly, we obtained low certainty of this evidence. The exact magnitude of the impact of physical training on the alteration of cardiac autonomic modulation in this patient population has yet to be conclusively defined.
Keywords: Cardiac autonomic modulation; Hemodialysis; Renal replacement therapy